Perencanaan Ruang Henti Khusus (RHK) Untuk Sepeda Motor Pada Persimpangan Bersinyal Jalan Sisingamangaraja – Jalan Pelangi – Jalan Turi Di Kota Medan: Studi Kasus - Rido Muhamad Affandi; Marwan Lubis; Hamidun Batubara (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Special stopping space for motorbikes is one of the facilities for motorbikes to stop at intersections during the red phase. This special stopping space has been tested on a limited scale to support the movement of motorbikes at signalized intersections in large cities in Indonesia. This research aims to evaluate the intersection and then plan a special stopping room according to the number of motorbikes piling up during the red phase at the intersection. Intersection evaluation is carried out based on primary data and secondary data. The calculation method is guided by the 1997 Indonesian Road Capacity Manual (MKJI) and Technical Planning Guidelines for Special Stop Spaces (RHK) for Motorcycles at Signalized Intersections in Urban Areas.The traffic behavior of the existing intersection is, west approach capacity 335 pcu/hour, DS (Degree of Saturation) 1,878, queue length 97 m and average delay 157 sec/pcu. East approach capacity is 342 pcu/hour, DS (Degree of Saturation) is 2,295, queue length is 97 m, and average delay is 169.3 sec/pcu. North approach capacity is 600 pcu/hour, DS (Degree of Saturation) is 0.546, queue length is 157 m, and average delay is 69.2 sec/pcu. South approach capacity is 941 pcu/hour, DS (Degree of Saturation) 0.987, queue length 245 m, and average delay 111.6 sec/pcu.The special stopping space design on the northern approach is 2 lanes with an approach lane and an area of ​​84 m2; on the southern approach, namely 2 lanes with an approach lane and an area of ​​84 m2; on the western and eastern approaches do not meet the 2012 Age Work Department Service standards in RHK planning.